2000
DOI: 10.1021/ma0005769
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Chitosan. 3. Hyperbranched Chitosan−Sialic Acid Dendrimer Hybrid with Tetraethylene Glycol Spacer

Abstract: Chitosan is a polysaccharide composed mainly of β-(1-4)-2-amino-2-deoxy-D-glucopyranose repeating units. Chitosan shows interesting biological properties such as immunological, 1 antibacterial, 2,3 and wound healing activity. 4 Moreover, it is a nontoxic 3 and biodegradable polymer, 5 and the free amino groups of chitosan offer great potential for further derivatization. Alternatively, dendrimers also offer several possibilities in molecular design owing to their multifunctional attachment sites. They have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…CS and PGA were chosen not only because they are biocompatible, but also because they offer the possibility of being easily conjugated with bioactive molecules. [33][34][35][36] The electrostatic assembly was confirmed by FT-IR measurements, and the adsorption process was monitored stepwise using UV-vis spectroscopy and a dissipation-enhanced quartz crystal microbalance (QCM-D). Because of the unique properties of CS and PGA, multilayer films composed of these substances are expected to be interesting for cell growth, such as muscle myoblast cells (C2C12).…”
Section: Introductionmentioning
confidence: 99%
“…CS and PGA were chosen not only because they are biocompatible, but also because they offer the possibility of being easily conjugated with bioactive molecules. [33][34][35][36] The electrostatic assembly was confirmed by FT-IR measurements, and the adsorption process was monitored stepwise using UV-vis spectroscopy and a dissipation-enhanced quartz crystal microbalance (QCM-D). Because of the unique properties of CS and PGA, multilayer films composed of these substances are expected to be interesting for cell growth, such as muscle myoblast cells (C2C12).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, full generation PAMAM dendrimers (G1-G3) were grafted onto chitosan through N-maleated chitosan by Michael type addition reaction. In comparison to the graft copolymer of Sashiwa et al [24,25], the graft copolymer reported in this paper is unique with respect to mode of preparation and properties. All the related properties such as its solubility, complexation with DNA, in vitro cytotoxicity and in vitro DNA release study were investigated in details in this paper.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, the chemical combination of chitosan with PAMAM dendrimers may provide novel biomaterial with improved water solubility, higher charge density and lower toxicity. Sashiwa et al [24,25] prepared chitosan-graft-PAMAM copolymers through tetraethylene glycol spacer by reductive Nalkylation, but till date, no report is available about N-maleated chitosan-graft-PAMAM copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Various classes of these compounds differing in composition and structures were reported, together with their practical use extending from targeting drug delivery, catalysis, and transport vehicles to synthetic vaccines. The main stress was given to glycopeptide dendrimers, namely multiple antigen glycopeptides (MAGs) [55][56][57][58]. An example of glycopeptide dendrimer synthesis, where lactose ligands were introduced to the surface of lysine-based dendrimer, was reported by Uryu et al ( Figure 11) [59].…”
Section: Figure 10mentioning
confidence: 99%